2017
DOI: 10.3892/or.2017.5925
|View full text |Cite
|
Sign up to set email alerts
|

A novel chalcone-based molecule, BDP inhibits MDA-MB-231 triple-negative breast cancer cell growth by suppressing Hsp90 function

Abstract: Triple-negative breast cancer (TNBC) is a molecularly diverse and heterogeneous disease and the molecular heterogeneity of TNBC increases the difficulty in improving survival rates. To date, therapeutic approaches for the treatment of TNBC such as hormonal chemotherapy and trastuzumab-based therapy have been limited by the lack of target receptors such as estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor 2 (Her2), emphasizing the urgent need for identifying new ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…These drugs represent a promising strategy for developing chalcones as novel anticancer agents. Recently, Jeong et al [ 218 ] and Oh et al [ 219 ] have shown that synthetic chalcones can have a heat-shock protein 90 (HSP90)-induced inhibitory effect, which opens new perspectives into cancer treatment through the destabilization proteins by which cancer cells survive and multiply (tumorigenesis) [ 220 ]. Several phase II clinical trials of new anticancer molecules that have two hydroxyl groups at positions 1 and 3 have revealed the inhibition of interactions between HSP90 and patient proteins through the binding of these molecules to the ATP site in HSP90 [ 221 , 222 ].…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…These drugs represent a promising strategy for developing chalcones as novel anticancer agents. Recently, Jeong et al [ 218 ] and Oh et al [ 219 ] have shown that synthetic chalcones can have a heat-shock protein 90 (HSP90)-induced inhibitory effect, which opens new perspectives into cancer treatment through the destabilization proteins by which cancer cells survive and multiply (tumorigenesis) [ 220 ]. Several phase II clinical trials of new anticancer molecules that have two hydroxyl groups at positions 1 and 3 have revealed the inhibition of interactions between HSP90 and patient proteins through the binding of these molecules to the ATP site in HSP90 [ 221 , 222 ].…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…Chalcone inhibits the growth of breast cancer cells by regulating the cell cycle and apoptosis 54 . A previous study discovered novel chalcone derivatives as potential inhibitors of epidermal growth factor receptor (EGFR) for treatment of bladder cancer 55 .…”
Section: Discussionmentioning
confidence: 99%
“…ERα has already been identified as a target for chalcones, especially in the field of cancer [17,33] and it is now well accepted that estrogens can protect against cardiovascular diseases [11,34,35]. At the vascular level, ERα pathway can, through a non-genomic mechanism, lead to an endothelium-dependent vasodilation [34,36].…”
Section: Discussionmentioning
confidence: 99%